AKREDITASI SEBAGAI KINERJA LEMBAGA PAUD UNTUK PENINGKATAN MUTU LAYANAN PAUD (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
Education for early child is education allotment for childs 0 – 6 age. Child want expanding if stimulasi according to age. Developing potensi slf child require to place pricise. The plece to price fo child is facility good and peaceful and balmy, educator adequate and price reached. The governmental pushing school/institusi for raising accredit thr managed trusted society as place price foe developing enthusiasm and talent. Acredit is result of performance instituse